Estudo da implantação do sistema de aproveitamento de águas pluviais para fins não potáveis em edificações - Garzão, Katia Aline (2013)
This work aimed to study the use of rainwater for purposes not drinkable. The capacity assessment study of rainwater collection was held in the city of Pato Branco, with the survey data of precipitation and temperature, the past 5 years, for an assessment of the drought and rainy periods, with the determination of the water balance. On the other hand a rainwater collection project in an existing residence, in which this tank was in an ofuro approximately 4 m³. For the calculation of the volume of the reservoir was used the method of Azevedo Netto, as NBR 15527 (ABNT 2007), the result was approximately 30.4 m³ of water. With the results of the evaluation of the water balance, it was found that on average, the city of Pato Branco, features 3 months of drought, but with average annual precipitation around 2000 mm, that indicate a precipitation compatible for the use of rainwater. Two were carried out bacteriological studies of rainwater, a water sample taken directly from the roof and another of water in its final destination, the internal tap, use for washing clothes, both samples had equal results, low amount of total coliforms and Escherichia Coli. In view of these data one can calculate an estimated value of expenses would have for the implementation and maintenance of this type of tank that was R$ 10929,22.